Exploring the Existence of Civic Dispositions in Junior High School Students: A Preliminary Study in Civic Education - Sukron Mazid; Atsani Wulansari; Kokom Komalasari; Aim Abdulkarim; Rahmat; Beti Indah Sari; Arum Nisma Wulanjani (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2026)
Civic disposition plays a crucial role in shaping students into responsible and active citizens, but its characteristics in the school environment require further study. This study aims to analyze the civic disposition of junior high school students and the factors influencing its development. A quantitative survey method was used involving 120 seventh-grade students from three public junior high schools in Magelang, Indonesia. A structured questionnaire measured five dimensions of civic disposition: responsibility, participation, politeness, empathy, and patience. The results showed that responsibility, politeness, and empathy were in the high category, while participation was in the medium category, and patience was the lowest dimension. These findings suggest that although students possess good ethical and social awareness, they still need encouragement to participate more actively in civic activities and to increase their patience in social interactions. Civic education should prioritize the balanced development of responsibility, participation, and patience to strengthen students' overall civic character. Recommendations are provided for strengthening learning programs that foster moral character and encourage active student involvement.